Analisis Marketing Mix pada BEN & BER Collection - Prima Vandayani; Taufik, Yuyun; Dwijayanti, Andina; Khadeeja; Rudi Kurniawan (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
This study aims to explore the marketing of mix Ben & Ber Collection at Garut. The marketing mix is one of the key factors in a company's success and can help achieve business objectives. The marketing mix, which consists of four main elements—product, price, promotion, and place—is an essential tool in planning and managing a company's marketing strategy to achieve its business goals. This study aims to describe the implementation of the marketing mix concept at Ben & Ber Collection in Garut City. This research employs a qualitative approach with a descriptive method. Data collection techniques include observation and interviews with respondents who are customers of Ben & Ber Collection uniforms. The results of the study indicate that the implementation of the marketing mix at Ben & Ber Collection in Garut City has been carried out effectively. This means that the marketing tools, including product, price, promotion, and place, as a whole, have supported Ben & Ber Collection in planning and managing the aspects of their marketing activities to achieve business objectives. However, despite most marketing mix indicators being considered well-implemented, there are still some indicators that have not been executed effectively.